Arthrospira platensis improves macrophages arginine metabolism and prevents insulin resistance in Psammomys obesus - Ghennai, Anissa; Koceir, Elhadj Ahmed; Aouichat-Bouguerra, Souhila; Bouderba, Saïda (Progress in Nutrition, 2018)
Introduction: Chronic low grade inflammation is generally linked to the development of obesity-related metabolic diseases and tissue-resident macrophages play a major role in the regulation of the inflammation markers in the tissues. The cyanobacterium Arthrospira platensis also named spirulina is a blue green microalgae which has anti-inflammatory and anti diabetic properties. This study aimed to evaluate its potential therapeutic benefits on insulin resistance and peritoneal macrophages arginine metabolism in experimental gerbils named Psammomys obesus. Methods: A control group was fed its vegetable -based low caloric diet (halophilic plants). Two experimental groups were fed a high caloric diet for 12 weeks. Spirulina, or its vehicle (0.9% NaCl solution) were administrated daily by gastric intubation during 12 weeks. At the end of experiments, serum was collected to assess biochemical parameters and arginine metabolism was studied from isolated peritoneal macrophages. Results: Spirulina attenuated hyperlipidemia and prevented hyperinsulinemia, avoiding metabolic disturbances. Psammomys fed a high caloric diet displayed macrophages arginine metabolism toward pro-inflammatory phenotype while spirulina supplementation maintained peritoneal macrophages’ iNOS activity similar to that of the control group. Conclusion: Our study suggests that Arthrospira platensis is effective in improving insulin sensitivity by regulating peritoneal macrophages’ arginine metabolism.